Environmental Programming of Susceptibility and Resilience to Stress in Adulthood in Male Mice - Peña, Catherine Jensen; Nestler, Eric J.; Bagot, Rosemary C. (Frontiers in Behavioral Neuroscience, 2019)
Epidemiological evidence identifies early life adversity as a significant risk factor for the development of mood disorders. Much evidence points to the role of early life experience in susceptibility and, to a lesser extent, resilience, to stress in adulthood. While many models of these phenomena exist in the literature, results are often conflicting and a systematic comparison of multiple models is lacking. Here we compare effects of nine manipulations spanning the early postnatal through peri-adolescent periods both at baseline and following exposure to chronic social defeat stress in adulthood, in male mice. By applying rigorous criteria across three commonly used measures of depression- and anxiety-like behavior, we identify manipulations that increase susceptibility to subsequent stress in adulthood and other pro-resilient manipulations that mitigate the deleterious consequences of adult stress. Our findings point to the importance of timing of early life stress and provide the foundation for future studies to probe the neurobiological mechanisms of risk and resilience conferred by variation in the early life environment.